Senior Administrators as legitimate partners in the strategic management of the University of Education, Winneba; an inside view - Hammond, Samuel Abieku; Agbo, Reginald Sitsofe Kwaku (Ghana Journal of Higher Education Management, 2024)
Strategic management of institutions of higher education largely unfold in the context of funding, increased emphasis on efficiency of resources, utilisation and management, and a strengthening of policy and planning roles of key administrators. Administrators in the Senior Member category are key in the planning and implementation of strategic management of the University. This paper attempts to tell the role played by Senior administrators in the University of Education, Winneba (UEW) as key partners in the strategic management of the institution. Senior Members in the UEW administration numbering 68, provided the data on the role they play in the strategic management of UEW and Version 16 of SPSS was used to analyse the data. It was realised that Senior Member administrators of UEW facilitate and implement the strategic plans and therefore play a very critical role in the strategic management of the university and, therefore should be considered as legitimate partners in the strategic management of UEW.